TIPOLOGI STRATEGI TRANSFORMASI DIGITAL PENJUALAN: STUDI LINTAS NEGARA TERHADAP PRAKTEK MANAJERIAL DAN DAMPAKNYA TERHADAP KINERJA: TIPOLOGI STRATEGI TRANSFORMASI DIGITAL PENJUALAN: STUDI LINTAS NEGARA TERHADAP PRAKTEK MANAJERIAL DAN DAMPAKNYA TERHADAP KINERJA - Yumna, Nailarania Zafira (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Digital transformation in the sales function has become a critical strategic element in facing the challenges of the digital era. This study aims to explore how companies’ managerial practices in managing digital sales transformation compare to existing prescriptive frameworks. Using a survey approach of 540 sales managers from the United States, United Kingdom, Germany, and Italy, and a cluster analysis based on five key dimensions—strategic clarity, sales force replacement, sales force empowerment, implementation actions, and key performance indicators—this study identifies four typologies of companies: Digital Sales Transformation Leaders, Laggards, Enablers, and Replacers. The results show that the success of digital transformation is influenced by a combination of strategic clarity, targeted use of technology, and a focus on customer value creation. This study provides a practical contribution in the form of a taxonomy that can be used as an evaluative and strategic tool for companies in designing and implementing effective digital sales transformation.